Underutilization of prescribed drugs use among first generation elderly immigrants in the Netherlands - Birnie Erwin; Koopmans Gerrit; Denktaş Semiha; Foets Marleen; Bonsel Gouke (BMC, 2010)
Abstract Background In developed countries, health care utilization among immigrant groups differs where the dominant interpretation is unjustified overutilization due to lack of acculturation. We investigated utilization of prescribed drugs in native Dutch and various groups of immigrant elderly. Methods Cross-sectional study using data from the survey "Social Position, Health and Well-being of Elderly Immigrants" (the Netherlands, 2003). Ethnicity-matched interviewers conducted the survey among first generation immigrants aged 55 years and older. Outcome measure is self-reported use of prescribed drugs. Utilization is explained by need, and by enabling and predisposing factors, in particular acculturation; analysis is conducted by multiple logistic regression. Results The study population consisted of immigrants from Turkey (n = 307), Morocco (n = 284), Surinam (n = 308) and the Netherlands Antilles (n = 300), and a native Dutch reference group (n = 304). Prevalence of diabetes mellitus (DM), COPD and musculoskeletal disorders was relatively high among immigrant elderly. Drug utilization in especially Turkish and Moroccan elderly with DM and COPD was relatively low. Drugs use for non-mental chronic diseases was explained by more chronic conditions (OR 2.64), higher age (OR 1.03), and modern attitudes on male-female roles (OR 0.74) and religiosity (OR 0.89). Ethnicity specific effects remained only among Turkish elderly (OR 0.42). Drugs use for mental health problems was explained by more chronic conditions (OR 1.43), better mental health (OR 0.95) and modern attitudes on family values (OR 0.59). Ethnicity specific effects remained only among Moroccan (OR 0.19) and Antillean elderly (OR 0.31). Explanation of underutilization of drugs among diseased with diabetes and musculoskeletal disorders are found in number of chronic diseases (OR 0.74 and OR 0.78) and regarding diabetes also in language proficiency (OR 0.66) and modern attitudes on male-female roles (OR 1.69). Conclusions Need and predisposing factors (acculturation) are the strongest determinants for drugs utilization among elderly immigrants. Significant drugs underutilization exists among migrants with diabetes and musculoskeletal disorders.